Communication experiences of Girl Up UI & UPNVJ in supporting women's empowerment - Khairunisa Anandhita Safira; Witanti Prihatiningsih (Jurnal Studi Komunikasi, 2025)
The rise of sexual abuse and violence that occur in campus environments often affect women. Minimal safe space for victims and unrest that fellow women have been haunted by frequent cases of abuse and sexual violence. In this case, it is necessary to have a massive involvement in addressing cases of gender abuse and equality through communities that are able to address, provide protection, and educate through various forms of communication media. Girl Up Community Universitas Indonesia (UI) & Girl Up UPN Veteran Jakarta (UPNVJ) plays an important role in addressing gender equality cases and women-related issues by supporting Women’s Empowerment in campus environments. Girl Up UI & Girl Up UPNVJ was selected as a research object because of significant involvement of women-related communication activities such as massive spread of information through digital platforms and face-to-face to the implementation of women empowerment programs in every area of life. The research also discussed communication media such as Instagram platform, Zoom Meeting, and Official Website used by Girl Up in socialising and educating the community and organising campaigns, especially in campus environments to be more concerned and able to address gender equality issues that should be fought for. The research used qualitative research methods conducted through a phenomenology approach with in-depth interview techniques and snowball sampling techniques. With a series of questions given to 6 (six) informants, it is found that the effectiveness of communication experience through online and offline platforms can become a communication tool and information dissemination to audiences. Girl Up UI and Girl Up UPNVJ successfully attract participants to support women's empowerment and to act on gender equality well.